More acceleration and less speed to assess physical demands in female young tennis players - Galé-Ansodi, C.; Castellano, J.; Usabiaga, O. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to describe the physical demands in match of female young tennis players, focusing on velocity and acceleration using microtechnology. Twenty-six female high-level young tennis players participated in the current study. Match-play played in official Tournament was codified using a global positioning system (10 Hz) that includes accelerometry (100 Hz). The results showed that: (1) the Estimation Distance (59.1 ± 24.8 m min-1) was overcome in 33% to the Real Distance (44.4 ± 7.7 m min-1); (2) the Acceleration Distance was around 89% of the Real Distance; (3) the 97.0 ± 6.1% of time and 90.9 ± 8.2% of distance covered by players were obtained in low speed zones (Positioning: 0-0.5 m s-1 and Jogging: 0.6-1.9 m s-1, respectively). The main conclusion of this study was that the two dimensions, velocity and acceleration, allowed to obtain complementary values of physical demands of tennis players. Nevertheless, acceleration dimension could give us more information about the intermittent profile of tennis players who are not able to reach high speeds. Therefore, tennis coaches should take into account the demands in both dimensions, specifically in acceleration/deceleration variables to design specific training tasks.